2003
DOI: 10.1152/japplphysiol.00958.2002
|View full text |Cite
|
Sign up to set email alerts
|

Altered myocardial Gsprotein and adenylyl cyclase signaling in rats exposed to chronic hypoxia and normoxic recovery

Abstract: The present work has analyzed the consequences of chronic intermittent high-altitude hypoxia for functioning of the G protein-mediated adenylyl cyclase (AC) signaling system in the right (RV) and left ventricular (LV) myocardium in rats. Adaptation to hypoxia did not appreciably affect the number of beta-adrenoceptors and the content of predominantly membrane-bound alpha-subunit (G(s)alpha) of the stimulatory G protein, but it raised the amount of cytosolic G(s)alpha in RV. The levels of myocardial inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
4
16
2
1
Order By: Relevance
“…Adaptation of adult rats to intermittent high-altitude hypoxia for 5 wk increased RV contractile function, determined as developed pressure, maximal rate of pressure development, and maximal rate of pressure fall (27). The increase of the same parameters in the LV as reported in this study suggests that they are caused by adaptation to hypoxia rather than by RV hypertrophy.…”
Section: Discussionsupporting
confidence: 67%
“…Adaptation of adult rats to intermittent high-altitude hypoxia for 5 wk increased RV contractile function, determined as developed pressure, maximal rate of pressure development, and maximal rate of pressure fall (27). The increase of the same parameters in the LV as reported in this study suggests that they are caused by adaptation to hypoxia rather than by RV hypertrophy.…”
Section: Discussionsupporting
confidence: 67%
“…On the other hand, there was a report that chronic hypoxia did not appreciably affect the content of the stimulatory G protein (9). In the present study, we found that the biologically active isoform, G s ␣ (45 kDa), was reduced in myocardium in CIHH rats, suggesting that the reduced activity of ␤-adrenergic receptor was related with the reduction of G s ␣ protein.…”
Section: Discussioncontrasting
confidence: 46%
“…The hypoxic decrease of ␤-AR density and function in the adult animal is reversible with normoxic recovery (11). However, exposure of the 1-day-old neonate to hypoxia over 10 days and subsequent normoxic recovery for 11 wk renders an adult animal that has a maintained receptor density but a lowered sensitivity to ␤-AR agonist stimulation (25).…”
Section: Discussionmentioning
confidence: 99%